Modelagem cinética da produção de biodiesel em estado supercrítico com catalisador heterogêneo - Brondani, Leoni Nogueira (2018)
The main objective of this study was to develop a kinetic model for catalytic supercritical reaction with methyl acetate to produce fatty acid methyl esters. Reaction models and estimated kinetic parameters were proposed for soybean oil and macaw oil reactional systems. An analysis method was developed to quantify the reaction components of both systems. An algorithm for model simulation and global optimization of kinetic parameters was implemented in MatLab® software, using a hybrid method for optimization by Particle Swarm Optimization (PSO) plus lsqnonlin and the ode15s routine, for resolution of EDO’s system. In first paper presented in this work, Arrhenius kinetic constants, activation energy (EA) and pre-exponential factor (k0) were adjusted to model proposed for reaction of soybean oil with methyl acetate catalyzed by Ca-Mg-Al mixed oxide. As results, it was discussed the influence of pre-critical and supercritical stages on reaction rates, the temperature influence in degradation rates of triacetin and triglycerides and the catalyst relevance in order to decrease required energy conditions and minimize unwanted degradation reaction. In second paper presented in this work, EA and k0 were adjusted to each reaction for reactional system of macaw oil with methyl acetate catalyzed by γ-alumina. As results, it was discussed the contribution of free fatty acids esterification and the acylglycerols interesterification to methyl esters production and the existence of parallel reactions between acetic acid and glycerol acetates. Through statistical validation, it was possible to prove that proposed models and estimated parameters offer a good fit for kinetic data obtained.